If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 2) = 3x + -17 Reorder the terms: 2(2 + 5x) = 3x + -17 (2 * 2 + 5x * 2) = 3x + -17 (4 + 10x) = 3x + -17 Reorder the terms: 4 + 10x = -17 + 3x Solving 4 + 10x = -17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + 10x + -3x = -17 + 3x + -3x Combine like terms: 10x + -3x = 7x 4 + 7x = -17 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + 7x = -17 + 0 4 + 7x = -17 Add '-4' to each side of the equation. 4 + -4 + 7x = -17 + -4 Combine like terms: 4 + -4 = 0 0 + 7x = -17 + -4 7x = -17 + -4 Combine like terms: -17 + -4 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 4(3x-4)+8=4x+32 | | 22=2(2x-1) | | 2x+23=5x+35 | | 7x+20=76 | | -3x-5=2(x-5) | | .30+1.19=2.99 | | 3.00+8.0=6.75 | | 15x-2*(5x-3)=2*(x+9) | | 4(36-12h+h^2)-18+3h-(144-18)= | | -7+3x=-34 | | 28-3c=14 | | 5=6x-1 | | y=x^4+1x^2-30 | | P=20-5Q | | x^4+1x^2-30=0 | | (10x+9)=3 | | 3*5*6=153072 | | 5x-7=7x+6 | | 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= | | 0=x^2-21x+24 | | 8-0.5(x+3)=0.25(x+-1) | | -(4-m)=10 | | 6=-4k+2 | | 20y+2=46 | | 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 |